CHARACTERISATION OF AmCCR1 AND pseudoCOMTAm PROMOTERS IN Acacia mangium - ABDUL LATIF, AZMAH; TAM, SHEH MAY; RATNAM, WICKNESWARI (Malaysian Applied Biology, 2020)
Acacia mangium is one of the most important species in forest plantation industry in Southeast Asia. Lignin is a complex polymer found in plant which has to be removed using harsh and toxic chemicals for the production of high quality paper. Understanding the complex pathway that underlies the regulation of lignin biosynthetic genes requires in depth knowledge of the genes involved and it’s regulatory elements. Using Thermal Asymmetric Interlaced PCR, a 770bp promoter of pseudoCOMTAm and 619bp of AmCCR1 promoter were isolated. Bioinformatics analysis revealed the presence of cis acting elements commonly found in lignin biosynthetic genes such as TATA box, CAAT box, W box, AC-I and AC-11 elements on both promoters.